The Image of Madurese Women in "Tandak" Short Story by Mahwi Air Tawar (NOBEL: Journal of Literature and Language Teaching, 2017)
Madurese belongs to some Indonesian ethnic groups that follow patriarchal system. The patriarchal hegemony is depicted in the short story entitled "Tandak" written by Mahwi Air Tawar. Therefore, the study aims to examine woman image in Madurese patriarchal system and symbolic resistance in the short story. The study uses descriptive research. The data sources are Tandak short story, books, and related articles. The data are collected by close reading technique. The collected data are analyzed by applying feminist literary criticism that views woman as a reader. The results show that the physical images of women in the short story are Madurese ideal women. The personality of each woman is varied. However, by comparing woman image and man image it can be found that woman is inferior, weak, and marginalized whereas man is superior, strong, and dominant. There are some symbolic resistances, but man's power still cannot be fully seized by woman.